PENYELESAIAN CAPACITATED VEHICLE ROUTING PROBLEM PADA PENDISTRIBUSIAN AIR GALLON MENGGUNAKAN ALGORITMA KOLONI LEBAH - BENI, YAKOBUS; FRAN, FRANSISKUS; YUDHI, YUDHI (E-Jurnal Matematika; Vol 13 No 3 (2024)DO - 10.24843/MTK.2024.v13.i03.p458, 2024)
Distribution is one of the problems in the business and industrial world, for example the problem of delivering supplies of raw materials and other goods to several customers, where the delivery must be carried out exactly once by one or more vehicles to each customer with a certain capacity. In its development, this problem was formulated as the Capacitated Vehicle Routing Problem (CVRP). Based on the definition, CVRP is one of the most common variations of the Vehicle Routing Problem (VRP) problem to determine the optimal route with the addition of constraints in the form of homogeneous vehicle capacity. Here, we discussed the CVRP problem of the distribution route for Pak Nurrofiq's gallons of water from the depot to its customers in the Taman Sei Raya Complex, Serdam Asri Complex and Kapuas Mas Complex. The aim of this research is to create a mathematical model for the CVRP problem in the distribution of Pak Nurrofiq's drinking water and solve it using the bee colony algorithm. The bee colony algorithm is a metaheuristic algorithm based on the behavior of honey bees in searching for food sources. The research results show that the case of gallon water distribution was successfully implemented into CVRP and completed using the bee colony algorithm, 4 routes were obtained with a total distance of all routes, namely 9,068 km.